SISTEM PAKAR DIAGNOSA PENYAKIT MATA GLAUKOMA DENGAN METODE TEOREMA BAYES - Niati, Endang; Sitohang, Sunarsan (LPPM Universitas Putera Batam, 2022)
Glaukoma is a disease in which eye pressure are abnormal or higher than normal causes damage to the opticnerve causing blindness that generally occurs in old age.but in the midst of the complexity, the lack of concern many people will eye health, prefer lifestyle and eating patterns that are instantaneous make eye disease glaukoma is currently sufferd by many yaoung people in the productive period.so increase the high eye diseases of glaukoma patients. Increased number of people with glaukoma eye dideases is dueto lack of knowledge about the symptoms of glaukoma eye disease, delay in handling and lack of experts or experts.so it takes the existence of an expert system to perform yhe diagnosis of glaukoma eye diases.user are asked to enter what symptoms are felt by the patient, then the system wil calculate the probality value of a disease and compare each probality of symptoms. Furthermore, the system will provide diagnostic result in the form of percentage, descriptions and treatment. This system is built on the web and implemented on the webserver . the percentage of system success l Keywords: Glaukoma,Expert System,Bayes Theorema.